The geography of consciousness in Ibsen's theatrical practice - Larson, Philip (Nordlit, 2015)
When a director stands in the cockpit of a rehearsal he or she sees a different object than a person reading the text of a play. This article attempts to outline a style of criticism that may be useful to persons preparing to produce Ibsen’s plays. Several critical principles are presented: first, that Ibsen’s plays have a systematic pattern of imagery; second, that Ibsen’s characters have a certain way of seeing the world, and that this way of seeing amounts to a psychology, what could now be termed a perceptual psychology; third, that the plays have a double action, one action motivated in the mature plays by the conventions of the well-made play, and the other action motivated by a mythic logic, in which the Ibsen character desires to see the world in a certain way. This desire can have potentially disastrous consequences if pursued too insistently, because of the disparity between a character’s mythic vision and the facts of life as it is actually lived.